Proving the Innocence of Prophet Noah in Facing His Son Based on the Appearances of the Verses with a Critique on the Theory of Allameh Tabatabai - mohammad daneshnahad; Mohammad Hasan Vakili (Comparative Theology)
One of the doubts about Noah's innocence is how this Holy Prophet asked to save his child, while God Almighty had previously forbidden him from such a request. Doesn’t such a request contradict the innocence of Prophet Noah, while he knew that his son was a disbeliever? Doesn't paying attention to relative relationships even in the case of disbelief contrast with the innocence of Prophet Noah? This research, with the method of collecting data, analyzing them, and comparing opinions aims to prove the innocence of Prophet Noah based on the appearances of the verses. In order to defend the innocence of Prophet Noah, Tabatabai as a religious scientist has given interpretations in this regard, including that Prophet Noah did not protest at all, while this is inconsistent with the appearances of the verses, and as long as the appearances of verses do not have any intellectual or narrative problems, it is necessary to rely on the authenticity of appearances. Keywords: Prophet Noah, Scientific and Practical Innocence, Polytheism, Asking for Forgiveness, Tabatabai. Introduction One of the basic doubts about Noah's innocence is his conversation with God Almighty regarding his son. Asking for the salvation of his child if he is a disbeliever is not compatible with the dignity of prophethood. The Holy Prophet should not seek the salvation of an unbeliever, even if that person is one of his children. Based on this, how can Noah's infallibility be summed up with his request to save his child? In order to answer this question, some scientists like Tabatabai tried to prove Noah's innocence by interpreting the verses, while the authors of this study believe that it is possible to prove Noah’s innocence based on the appearances of the verses without the need for misinterpretation. Interpretation is acceptable when the appearances of the verses are inconsistent with definite rational and narrative proofs. Materials and Methods The method of this research is based on collecting data, analyzing them, and comparing the opinions of experts with the aim of proving the innocence of Prophet Noah based on the appearances of the verses. Research FindingsThe results of the present study showed that:People, during the life span of Noah’s prophethood, in terms of internal characteristics, were afflicted with disbelief, disobedience, sin, misguidance, and cruelty. In terms of external characteristics, they considered Noah to be clearly misguided and insane; they denied and ridiculed him and did not value God Almighty.The son of Noah, based on the talks of Prophet Noah, had a relationship with unbelieving people, and therefore all their attributes can be transmitted to him, Prophet Noah knew about his son's disbelief, and based on the appearances of the verses, this cannot be denied.The selected theory about Noah's infallibility is based on the fact that Noah tried to save his son due to his unparalleled patience and God's promise to save his family, and what he did not know about was not his son's disbelief but not being saved and not being a believer. Such a lack of knowledge does not affect his innocence. Discussion of Results and ConclusionAccording to the characteristics mentioned for Noah's people in the Holy Qur'an, accompanying Noah's son with such a people that is expressed by Noah, and in addition to this, the answer that the son of Noah gives to Noah, it can be concluded that Prophet Noah was aware of his son's disbelief. But due to his tolerance and high existence from a position and God's promise to save his family from divine punishment, this false impression arose for Prophet Noah that his son would be one of the saved, while such an idea was incorrect. This misconception does not cause any disturbance to the infallibility of Prophet Noah, because this notion did not cause Noah to leave the path of worship and monotheism, but based on divine zeal and high tolerance, he sought to save his son in such a way that he first became a Muslim who may be saved from God's punishment. Otherwise, the dignity of this prophet is higher than a man who only considers relative relationships without considering faith and disbelief and prefers the life of his unbelieving child over other people. In addition, if there was such a view, he would never have publicly asked the Almighty God to destroy all the infidels only because of his unparalleled patience that he makes such a request from Almighty God. As we can see from the requests of Prophet Ibrahim towards his uncle and from the Holy Prophet towards some infidels, we can interpret Noah's request in this direction. Such requests are only due to the firm determination and existence capacity of these prophets who have sought to attract the maximum number of people to the path of monotheism.